Comparison study and synthetic evaluation of combined injection in a spark ignition engine with hydrogen-blended at lean burn condition. (15th August 2018) - He, Fengshuo; Li, Shuo; Yu, Xiumin; Du, Yaodong; Zuo, Xiongyinan; Dong, Wei; Sun, Ping; He, Ling
Abstract: This study contributes to synthetic improvement and evaluation of energy efficiency and cleaner production by using combined injection in a gasoline-hydrogen blended engine bench. According to the previous published literature, few researches deal with combined injection technology, especial hydrogen combined injection. The equivalence ratio was kept at 0.77 and the energy input into the engine was constant. Some main conclusions were got that as for the PFI + GDI mode and the GDI mode, higher injection pressure could lead to longer spray penetration distance and better atomization, but excessive direct injection pressure may cause spray wall impingement and deteriorate the engine emissions performance. As for the PFI + HDI mode (90% gasoline and 10% hydrogen, energy ratio), a small amount hydrogen could improve the engine torque effectively and rise 5.34% than the PFI mode in average value and further reduce CO by 13.98%, HC emissions by 30.03%, but increase NOx emissions by 179.31% than the PFI mode. After hydrogen addition, increase of the direct injection pressure could suppress the forming of the accumulation mode particles. In the range of accumulation mode, the particle number (PN) concentration of the PFI + HDI mode reduced 26.1% than the PFI mode, reduced 35.66% than the PFI + GDI mode and reduced 12.28% than the GDI mode. Meanwhile, a comprehensive evaluation of different injection modes were obtained. Highlights: Combined injection with hydrogen can effectively increase torque output. Combined injection improves CO and HC emissions, but deteriorates NOx emissions. Injection pressure has a greater impact on gasoline (GDI) than hydrogen (HDI). Hydrogen can inhibit the formation of accumulation mode particles.